2010
DOI: 10.1007/s11431-010-3146-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the stability and 3-dimensional character for natural convection in a rectangular cavity heated from below

Abstract: Natural convection of air is numerically simulated in a 3-dimensional rectangular cavity heated from below using SIMPLE algorithm with a QUICK scheme. The results suggest that when all lateral walls are adiabatic, the fluid rolls occur along the long axis. When the Rayleigh number is smaller, the flow is of 2-dimensional character, and the rolls shapes are similar. The average Nusselt numbers in the central part of the cavity are similar. The average Nusselt numbers in the part near by the cavity are different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The governing equations are solved in primitive variables and two-dimensionally staggered grid based on the control volume method [7] . The SIMPLE algorithm with a QUICK scheme is used to solve the coupled heat transfer and fluid flow problem [8] .…”
Section: Testing Grid and Time Stepmentioning
confidence: 99%
See 2 more Smart Citations
“…The governing equations are solved in primitive variables and two-dimensionally staggered grid based on the control volume method [7] . The SIMPLE algorithm with a QUICK scheme is used to solve the coupled heat transfer and fluid flow problem [8] .…”
Section: Testing Grid and Time Stepmentioning
confidence: 99%
“…Every 10 point is analyzed. (a) The reconstructed phase space of time series The time series (7) is reconstructed a m-dimensional phase space by using time difference method. ,...... 2 , 1 ), , ,…”
Section: Calculating Correlation Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bifurcation appeared under the smaller heat flux, and disappeared under the larger heat flux. Zhan [11] conducted a numerical investigation on the nonlinear phenomenon of natural air convection in a 3-D rectangular cavity which was heated underneath by SIMPLE algorithm with QUICK scheme. The results showed that the static and dynamic bifurcation appeared with different initial conditions.…”
Section: Introductionmentioning
confidence: 99%